A Case–Referent Study of Lung Cancer and Incense Smoke, Smoking, and Residential Radon in Chinese Men - Tse, Lap Ah (National Institute of Environmental Health Sciences, 2011)
Background: Burning incense generates large amounts of air pollutants, many of which are confirmed or suspected human lung carcinogens. Objectives: We conducted a population-based case–referent study to examine the effect of incense smoke exposure on lung cancer risk among Chinese males and explored the joint effect of cigarette smoking and exposure to residential radon. Methods: We recruited 1,208 male lung cancer incident cases and 1,069 community referents from 2004 to 2006 and estimated their lifetime exposures to incense smoke and other residential indoor air pollutants based on self-reported information collected during interviews. We performed unconditional multivariable logistic regression analysis to estimate the odds ratio (OR) for lung cancer associated with exposure to incense smoke after adjusting for possible confounders. We conducted stratified analyses by smoking status and exposures to incense burning and residential radon and explored the potential additive-scale interactions. Results: We observed an association between incense exposure and lung cancer that was limited primarily to smokers. Cigarette smoking and high cumulative incense exposure at home appeared to have a synergistic effect on lung cancer (compared with never-smokers who never used incense, the OR for lung cancer for smokers who used incense ≥ 60 day-years = 5.00; 95% confidence interval: 3.34, 7.51). Power was limited, but we also found preliminary evidence suggesting that radon exposure may increase risk among smokers using incense. Conclusion: Our study suggests that exposure to incense smoke in the home may increase the risk of lung cancer among smokers and that exposure to radon may further increase risk.